Anterolateral defect of left congenital diaphragmatic hernia with hepatic herniation - Yuta Takeuchi; Seiichiro Inoue; Akio Odaka; Yuki Muta; Yoshifumi Beck (Elsevier, 2022)
Anterolateral defect of the diaphragm is an extremely rare type of congenital diaphragmatic hernia (CDH). We report our experience with a rare anterolateral type of CDH.His birth weight was estimated as 2700 g. A CDH was suspected on fetal ultrasound at 20 weeks' gestation. Fetal MRI performed at 34 weeks and 1 day of gestation showed elevation of the intestinal tract, stomach, and outer left lobe of the liver. A boy was delivered by caesarian section at 37 weeks and 0 days of gestation. Surgery was performed on the fourth day after delivery. The dorsal muscle bundle was well developed, but the ventral diaphragm was deficient, and a diagnosis of anterolateral type CDH was made. The size of the diaphragmatic defect was 5 × 3 cm. On the 15th day after surgery, the tracheal tube was extubated, and the patient was discharged 51 days after delivery. The patient is still being followed up, but no signs of recurrence have been observed.We experienced a case of an unusual form of left anterolateral CDH. The postnatal course was relatively stable, although a severe form was predicted due to the presence of hepatic elevation.